A Novel Bio-Inspired Ag/3D-TiO2/Si SERS Substrate with Ordered Moth-like Structure - Jingguo Yang; Florian Ion Tiberiu Petrescu; Ying Li; Dandan Song; Gang Shi (Nanomaterials, 2022)
This paper reports a novel method to fabricate a bio-inspired SERS substrate with low reflectivity, ultra-sensitivity, excellent uniformity, and recyclability. First, double layers of polystyrene spheres with different particle sizes were assembled on the surface of a silicon wafer to act as a moth-like template. Second, through the template sacrifice method, the TiO2 film with a three-dimensional moth-like eye structure was induced by the double-layer polystyrene spheres in the previous step, and its microscopic morphology showed a high degree of order. Finally, Ag nanoparticles were assembled on the TiO2 film to form a bio-inspired SERS substrate. This ordered bio-inspired structure can not only reduce reflection, but also reinforce the uniformity of hotspot density, which helps to improve the sensitivity and uniformity of the Raman signal. This bio-inspired SERS substrate can detect R6G molecules at a concentration as low as 1.0 × 10−10 mol/L, and its enhancement factor (EF) can reach 6.56 × 106. In addition, the composite of Ag and TiO2 can realize the photocatalytic degradation of R6G and then realize the recyclability of the SERS substrate.